What is the solution of the differential equation # dy/dx = 2y(5-3y) # with #y(0)=2#?

Answer 1

# y = (10e^(10x))/(6e^(10x)-1) #

We have:

# dy/dx = 2y(5-3y) #

We can "separate the variables" in this First Order Separable ODE to obtain

# int \ 1/(y(5-3y)) \ dy = int \ 2 \ dx #

By breaking down the integrand into partial fractions, it is possible to integrate the LHS while the RHS remains trivial.

# 1/(y(5-3y)) -= A/y+ B/(5-3y) # # " " = (A(5-3y)+By)/(y(5-3y)) #

Getting to the answer:

# 1 -= A(5-3y)+By #
Where #A,B# are constants that are to be determined. We can find them by substitutions (In practice we do this via the "cover up" method:
Put # y =0 => 1=5A => A=1/5# Put # x = 5/3 => 1 = (5B)/3 => B = 3/5 #

Thus, we can now write:

# \ \ \ \ \ \ \ \ \int \ (1/5)/y + (3/5)/(5-3y) \ dy = int \ 2 \ dx #
# :. 1/5 int \ 1/y - 3/(3y-5) \ dy = int \ 2 \ dx #

And after integrating, we obtain:

# 1/5 { ln|y| - ln|3y-5|} = 2x + C #
Using the initial condition #y(0)=2# then:
# 1/5 { ln2 - ln1} = C => C= 1/5ln 2#

Thus, we have:

# 1/5 { ln|y| - ln|3y-5|} = 2x + 1/5ln 2 #
# :. ln|y| - ln|3y-5| = 10x + ln 2 #
# :. ln|y/(3y-5)| = 10x + ln 2 #
# :. y/(3y-5) = e^(10x + ln 2) #
# :. y = (3y-5) 2e^(10x) #
# :. y = 6ye^(10x) - 10e^(10x) #
# :. 6ye^(10x) - y = 10e^(10x) #
# :. (6e^(10x)-1)y = 10e^(10x) #
# :. y = (10e^(10x))/(6e^(10x)-1) #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

#y(x) = 10/(6-e^(-10x))#

This differential equation can be separated:

#dy/dx = 2y(5-3y)#
#dy/(2y(5-3y)) = dx#
#(1) " " int dy/(2y(5-3y)) = int dx#
Solve the integral in #y# using partial fractions:
#1/(2y(5-3y)) = A/(2y) + B/(5-3y)#
#1/(2y(5-3y)) = (A(5-3y)+2By)/(2y(5-3y))#
#y(2B-3A) +5A=1#
#{(2B-3A=0),(5A=1):}#
#{(A=1/5),(B=3/10):}#
#int dy/(2y(5-3y)) = 1/10int dy/y+3/10int dy/(5-3y)#
#int dy/(2y(5-3y)) = 1/10(int dy/y-int (d(5-3y))/(5-3y))#
#int dy/(2y(5-3y)) = 1/10(lnabsy-lnabs(5-3y)) + C#
#int dy/(2y(5-3y)) =-1/10lnabs(5/y-3) + C#
Substituting in #(1)#:
#x = -1/10lnabs(5/y-3) + C#
#-10x+C =lnabs(5/y-3) #
#ce^(-10x) = 5/y-3#
#5/y =3+ce^(-10x)#
#y =5/(3+ce^(-10x))#
For #x=0# the initial condition is #y(0)=2#, so:
#2=5/(3+c)#
#c=-1/2#

Then, the necessary resolution is:

#y(x) = 10/(6-e^(-10x))#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

The solution to the given differential equation ( \frac{dy}{dx} = 2y(5 - 3y) ) with the initial condition ( y(0) = 2 ) is:

[ y(x) = \frac{5e^{10x}}{3e^{10x} + 1} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7